2018
DOI: 10.1590/2179-8087.026715
|View full text |Cite
|
Sign up to set email alerts
|

Forests of the Iguaçu National Park: Structure, Composition, and Richness

Abstract: Considering the importance of the Iguaçu National Park for the conservation of the Atlantic Forest and the absence of scientific or technical studies characterizing the ecology of forest species after seven and a half decades of its existence, a phytosociological survey of the arboreal vegetation was conducted to identify the various existing species and their successional stages. A total of 54 families, 135 genera, and 218 species were found in this survey. Euterpe edulis Mart. was the most frequently occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The study by Estevan et al [74] in fragments of Seasonal Semideciduous Forest in northern Paraná also showed resemblances with the present study, the most important species were the same: Trichilia clausseni, C. canjerana; Nectandra megapotamica; S. bonplandii and G. kunthiana. When considering the density, resemblances are also observed with the study by Souza et al (2019) [72], with an abundance of S. bonplandii, N. megapotamica, C. canjerana and B. riedelianum.…”
Section: Floristics and Phytosociologysupporting
confidence: 70%
See 2 more Smart Citations
“…The study by Estevan et al [74] in fragments of Seasonal Semideciduous Forest in northern Paraná also showed resemblances with the present study, the most important species were the same: Trichilia clausseni, C. canjerana; Nectandra megapotamica; S. bonplandii and G. kunthiana. When considering the density, resemblances are also observed with the study by Souza et al (2019) [72], with an abundance of S. bonplandii, N. megapotamica, C. canjerana and B. riedelianum.…”
Section: Floristics and Phytosociologysupporting
confidence: 70%
“…Many resemblances in species composition exist when compared with other studies in nearby areas of Seasonal Semideciduous Forest [70,71,74] and transitional areas between Semideciduous and Mixed Forests [72,73,78] (Appendix 2); however, there are differences in the structure of the communities, mainly in the species that present the highest abundances and IV, probably due to the different conditions of each area, whether related to the environment or anthropic activities.…”
Section: Floristics and Phytosociologymentioning
confidence: 75%
See 1 more Smart Citation
“…located on the border of the states of Rio de Janeiro and Minas Gerais (Souza et al, 2015(Souza et al, , 2018Ribeiro et al, 2019). This richness may be a reflection of the mosaic of environments, at different stages of ecological succession, observed in the study area (Souza et al, 2019), which may favor synanthropic species and those more frequent in environments under lower human pressure and less fragmented areas (Souza et al, 2010;Oliveira et al, 2017;Clemente et al, 2021;Coelho et al, 2022).…”
Section: Resultsmentioning
confidence: 91%
“…Before this study, 28 species were recorded for the park, in the management plan (IBAMA, 1999), phytosociological studies (Gris & Temponi 2017;Gris et al 2014;Souza et al 2019), and in a checklist for ParNa Iguaçu (Trochez et (IBAMA 1999;Gris et al 2014;Gris & Temponi 2017;Souza et al 2017Souza et al , 2019Trochez et al 2017). Confirmed indicates that species were either recollected or identifications on herbarium specimens were confirmed.…”
Section: Psidium Striatulummentioning
confidence: 99%